2020
DOI: 10.1002/jcp.29667
|View full text |Cite
|
Sign up to set email alerts
|

LINC02535 co‐functions with PCBP2 to regulate DNA damage repair in cervical cancer by stabilizing RRM1 mRNA

Abstract: Cervical cancer (CC) is one of the commonest malignant cancers among women with high morbidity and mortality. Despite encouraging advances had been found in diagnostic and therapeutic strategies, effective therapeutic strategy and further exploration of the mechanism underlying in CC is still needed. We searched The Cancer Genome Atlas database and found that long noncoding RNA LINC02535 was highly expressed in CC. LINC02535 has not been studied in CC, and its molecular regulation mechanism remains unknown. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
(29 reference statements)
2
22
0
Order By: Relevance
“…The cell cycle, cAMP signalling pathway and homologous recombination were enriched in the KEGG pathway analysis (Figure 2A, Table ). These findings suggest that LINC02535 target genes are closely related to cell growth–related pathways in PDGC progression, which is consistent with previous reports on the important role of LINC02535 in cervical cancer 16 . A heat map showing gene expression in paracancerous tissues, as well as in gastric cancer tissues, indicated that transcripts of ten genes (TM4SF20, CHRNA1, CEACAM18, RHCG, IL17C, SLC30A10, SAA1, SAA2, FEZF1, ALDH3B2 and LINC02535) that participate in cell growth were significantly increased in gastric cancer tissues compared with paracancerous tissues (Figure 2B).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The cell cycle, cAMP signalling pathway and homologous recombination were enriched in the KEGG pathway analysis (Figure 2A, Table ). These findings suggest that LINC02535 target genes are closely related to cell growth–related pathways in PDGC progression, which is consistent with previous reports on the important role of LINC02535 in cervical cancer 16 . A heat map showing gene expression in paracancerous tissues, as well as in gastric cancer tissues, indicated that transcripts of ten genes (TM4SF20, CHRNA1, CEACAM18, RHCG, IL17C, SLC30A10, SAA1, SAA2, FEZF1, ALDH3B2 and LINC02535) that participate in cell growth were significantly increased in gastric cancer tissues compared with paracancerous tissues (Figure 2B).…”
Section: Resultssupporting
confidence: 93%
“…We also assessed the functions of the novel lncRNA LINC02535 and found that LINC02535 promoted gastric cancer cell progression in vitro. To the best of our knowledge, only one other similar study showed that LINC02535 was correlated with cervical cancer 16 . The study found significantly higher LINC02535 and poly(C)‐binding protein 2 (PCBP2) expression in cervical cancer tissues and that LINC02535 and PCBP2 costabilized RRM1 mRNA to facilitate DNA repair damage and promote cell proliferation and epithelial‐to‐mesenchymal transition.…”
Section: Discussionmentioning
confidence: 88%
“…It inhibits the repair of DNA damage in cervical cancer cells and furthers the process of EMT. Ultimately, it promotes the occurrence and development of cervical cancer (Wen et al, 2020). AL034397.3 was found to be correlated with autophagy in LUAD.…”
Section: Discussionmentioning
confidence: 89%
“…AC024022.1 is the protective biomarker in papillary renal cell carcinoma [23]. LINC02535 co-functions with PCBP2 to regulate DNA damage repair in cervical cancer by stabilizing RRM1 mRNA [24]. LINC02535 is highly expressed in Lung Adenocarcinoma tissues and closely related to the OS of LUAD.…”
Section: Discussionmentioning
confidence: 99%